Impact of Bacillus Inoculation on Rhizosphere Bacterial Community Structure: A Review - Nisrina Salsabila; Reginawanti Hindersah (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2024)
The rhizosphere is a specialized zone where plant roots interact with the soil microbiome. Among various beneficial microbes, the genus Bacillus stands out due to its diverse functionalities and potential to boost plant growth and resilience. Bacillus is a key genus of plant growth-promoting rhizobacteria (PGPR) known for enhancing nutrient availability, producing phytohormones, and inducing plant resistance to pathogens. Inoculating Bacillus species into the rhizosphere can significantly alter the bacterial community's structure and composition. These alterations are driven by the competitive and cooperative interactions between Bacillus and the native rhizosphere microorganisms. Incorporating soil microorganisms into the host plant's beneficial bacterial community improves soil nutrient cycling and nutrient use efficiency. Using microbial inoculants is an effective strategy to address crop succession challenges, enhance microbial community structure, and improve soil fertility, thereby promoting crop growth. This review thoroughly examines the current understanding of how Bacillus inoculation impacts rhizosphere bacterial community structure.